Branched copolymers as additives for reducing the viscosity of mineral binder compositions - Patents.com
By preparing branched copolymer additives without epoxypropane, the flowability and viscosity of low w/b ratio concrete are solved, and the rapid flow and low viscosity of high-performance concrete are achieved, which is suitable for high-performance concrete, ultra-high-performance concrete and self-solid concrete.
Patent Information
- Application Number
- JP2022524265
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-29
- Filing Date
- 2020-11-25
- Publication Date
- 2025-02-06
- Estimated Expiration
- 2040-11-25
AI Technical Summary
The prior art is difficult to effectively improve the fluidity and reduce viscosity of low water/mineral bond ratio (w/b ratio) concrete while avoiding the problems of moisture reduction and solidification delay, especially in high-performance concrete (HPC), ultra-high-performance concrete (UHPC) and self-condensed concrete (SCC).
The branched copolymer with specific structures is prepared through a multi-step synthesis process, including the reaction of alcohols, amines, carboxylic acids or amides with epoxychlorohydrin or glycidyl to form a branched copolymer without epoxychlorohydrin, which is used to increase fluidity and reduce viscosity.
It achieves significant improvement in fluidity and viscosity without changing the fluidity and collapse, reduces component separation and gas input, and does not affect water demand. It is suitable for high-performance flowing agents such as polycarboxylic acid ethers, avoiding the use of epoxypropane.
Smart Images

Figure 0007627691000001 
Figure 0007627691000002 
Figure 0007627691000003
Abstract
Description
[Technical field]
[0001] The present invention relates to the use of a branched copolymer as an additive to increase the flow rate and reduce the viscosity of a mineral binder composition. Further aspects of the invention relate to a mineral binder composition and a hardened shaped body comprising the branched copolymer. [Background technology]
[0002] Dispersants or flow agents are used in the building industry as plasticizers or water-reducing agents for binder compositions such as, for example, concrete, mortar, cement, gypsum, and lime. The dispersants used are generally organic polymers that are added in solid form to the mixing water or mixed with the binder composition. In this way, it is advantageous to be able to modify both the consistency of the binder composition during processing and its properties in the hardened state.
[0003] The selection and dosage of a suitable dispersant depends, inter alia, on the specific composition, processing method, or end use of the binder composition. In particular, in the case of certain binder compositions, such as, for example, special concretes or special mortars, this is a demanding task.
[0004] Special concretes include in particular concretes produced with a low water / mineral binder ratio (w / b ratio), i.e. based on mineral binders and containing very little water, such concretes are in particular high performance concretes (HPC), ultra high performance concretes (UHPC) and / or self-compacting concretes (SCC).
[0005] An important advantage of SCC is that it flows rapidly without segregation simply under gravity, automatically filling cavities and losing air without the application of compression energy, and therefore does not need to be vibrated as is the case with conventional concrete. Self-compacting concrete is therefore particularly advantageous when high placement performance is required, in demanding geometries, in the case of dense mesh reinforcement, when the thickness of the parts is low, or in situations where the application of additional compression energy is possible only with difficulty, if at all.
[0006] A further advantage of concrete with a low w / b ratio is that it has a low porosity, especially in the hardened state, which allows for particularly high strength.
[0007] However, after being constituted with water, such concretes with low w / b ratios also have undesirably high viscosity and stickiness, and therefore the production, handling and application of such concretes is often particularly time and energy consuming.
[0008] In practice, superplasticizers in the form of polycarboxylate ethers (PCEs) are typically used to improve the flow properties of mineral binder compositions. Conventional PCEs usually exhibit a significant reduction in the water level and thus reduce the yield point of the mineral binder composition, but only have a small, if any, effect on the viscosity. Furthermore, PCEs typically have a retarding effect on the hydration and thus develop the strength of the mineral binder.
[0009] Thus, EP 2986580 describes the use of certain PCEs to increase the flow rate and / or reduce the viscosity of mineral binder compositions. Comb polymers are characterized by a low molar mass of side chains and a low molar ratio of side chains to acid groups in the polymer backbone. However, these PCEs also reduce the water demand of the mineral binder, bringing about a retarding effect on it.
[0010] WO 2010 / 112775 describes branched polyethers with phosphonic acid end groups, where branching is achieved by the incorporation of nitrogen groups into the polymer structure. The described polyethers reduce the viscosity of fresh concrete. The disadvantage, however, is that, especially in concretes with low w / b ratios, these polyethers typically have little effect on the yield point or slump, despite the need to use high dosages, and often have high retarding and water-reducing properties.
[0011] Finally, EP 2964586 describes copolymers as dispersants for mineral binders, which contain units derived from (i) an ethylenically unsaturated acid and (ii) an ethylenically unsaturated branched polyether macromonomer. These dispersants have the disadvantage that they are produced using epichlorohydrin, which is difficult to handle. Furthermore, these copolymers often result in an unwanted additional air input, which also results in a reduction in the water demand of the mineral binder. Summary of the Invention [Problem to be solved by the invention]
[0012] Therefore, there is still a need for additives for mineral binder compositions, especially for concrete or mortar with low w / b ratios, which ensure optimal rheology of these mineral binder compositions and therefore their processing properties, which are readily available. More specifically, there is a need for additives to increase the flow rate and reduce the viscosity of mineral binder compositions. At the same time, it would be advantageous if these additives had very low water-reducing capacity, if any at all. [Means for solving the problem]
[0013] The object of the present invention is to provide an additive for mineral binder compositions (inorganic binder compositions), in particular for concrete or mortar at low w / b ratios, which allows a controlled increase in the flow rate and a decrease in viscosity of the mineral binder composition. If possible, this should leave the further properties of the mineral binder composition unchanged, in particular the spread, slump or yield point. Preferably further, the additive should be able to be used together with other additives, in particular with superplasticizers such as PCE.
[0014] Surprisingly, it has been found that this object is achieved by using a copolymer as an additive as claimed in claim 1.
[0015] The present invention therefore relates to the use of a copolymer as an additive for increasing the flow rate and / or reducing the viscosity of a mineral binder composition, in which case the copolymer can be prepared in a multi-stage operation comprising the following steps: (1) optionally, a compound of the general formula R 1 A starting material S selected from the group consisting of alcohols, amines, carboxylic acids or amides of formula -XH is reacted with an alkoxylating agent and / or a halogenated alcohol or halogenated amine Hal-R 2 -XH, wherein R 1 = C1-C18 alkyl, C2-C18 alkylene, C3-C10 cycloalkyl, C6-C30 aryl, C7-C30 aralkyl or C1-C18 carbonyl, X = O or NH, Hal = Cl, Br or I, and R 2 =C1-C16 alkyl; (2) General formula R 1 reacting a starting material S selected from the group consisting of alcohols, amines, carboxylic acids or amides of formula -XH or the reaction product of step (1) with glycidol or epichlorohydrin or a mixture of glycidol and an alkoxylating agent or a mixture of epichlorohydrin and an alkoxylating agent, wherein R 1= C1 to C18 alkyl, C2 to C18 alkylene, C3 to C10 cycloalkyl, C6 to C30 aryl, C7 to C30 aralkyl or C1 to C18 carbonyl, X = O or NH; (3) Optionally, reacting the reaction product of step (2) with an alkoxylating agent.
[0016] A particular advantage of the use of the copolymers of the invention as additives in mineral binder compositions is the increased flow rate or reduced viscosity of the composition at substantially unchanged spread or slump compared to a mineral binder composition of the same composition but without the copolymers of the invention. More specifically, the increased flow rate or reduced viscosity can be achieved at substantially unchanged spread and / or slump in mineral binder compositions with low w / b ratios.
[0017] Further advantages of the use of the copolymers of the invention as dispersants in mineral binder compositions are less segregation or separation of the components of the mineral binder composition, less undesirable air incorporation, and no significant intrinsic water-reducing ability of the copolymers, the latter being important since the copolymers of the invention can thus be combined with known water-reducing agents, for example superplasticizers such as lignosulfonates, polynaphthalenesulfonates, polymelaminesulfonates and / or polycarboxylic acid ethers, in existing formulations without the need to adjust the dosage of the water-reducing agent.
[0018] Finally, the copolymers of the present invention are notable for their ease of synthesis, preferably without the need for the use of epichlorohydrin, which is an advantage since epichlorohydrin is problematic due to its toxicity and carcinogenicity.
[0019] Further aspects of the invention are the subject matter of the other independent claims. Particularly preferred embodiments of the invention are the subject matter of the dependent claims. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] A first aspect of the invention relates to the use of a copolymer as an additive for increasing the flow rate and / or reducing the viscosity of a mineral binder composition, in which case the copolymer can be prepared in a multi-stage operation comprising the steps of: (1) optionally, a compound of the general formula R 1 A starting material S selected from the group consisting of alcohols, amines, carboxylic acids or amides of formula -XH is reacted with an alkoxylating agent and / or a halogenated alcohol or halogenated amine Hal-R 2 -XH, wherein R 1 = C1-C18 alkyl, C2-C18 alkylene, C3-C10 cycloalkyl, C6-C30 aryl, C7-C30 aralkyl or C1-C18 carbonyl, X = O or NH, Hal = Cl, Br or I, and R 2 =C1-C16 alkyl; (2) General formula R 1 reacting a starting material S selected from the group consisting of alcohols, amines, carboxylic acids or amides of formula -XH or the reaction product of step (1) with glycidol or epichlorohydrin or a mixture of glycidol and an alkoxylating agent or a mixture of epichlorohydrin and an alkoxylating agent, wherein R 1 = C1 to C18 alkyl, C2 to C18 alkylene, C3 to C10 cycloalkyl, C6 to C30 aryl, C7 to C30 aralkyl or C1 to C18 carbonyl, X = O or NH; (3) Optionally, reacting the reaction product of step (2) with an alkoxylating agent.
[0021] More specifically, the use of the copolymers of the invention increases the flow rate and reduces the viscosity of the mineral binder composition. Moreover, it is particularly advantageous that the copolymers of the invention do not contribute, at least not significantly, if at all, to reducing the water demand of the mineral binder composition.
[0022] The measure used for the reduction in viscosity in this context is the reduction in the flow time or funnel flow time according to DIN EN 12350-9 and / or the reduction in the running time according to JSCE-F 541-1999. The shorter the flow time / funnel flow time and / or the running time, the lower the viscosity of the mineral binder composition. A further measure of the reduction in viscosity in this context is the increase in the flow rate, measured according to Swiss standard SIA 262.238 or as t500 according to Japanese standard JIS A1150. An increased flow rate therefore means a lower viscosity of the mineral binder composition.
[0023] The term "water demand" in the present context is understood to mean the amount of water required to establish a certain spread, in a given binder composition, measured according to standard DIN EN 12350-5.
[0024] In the case of the inventive use of the copolymers as additives for mineral binder compositions, mineral binder compositions composed of water containing these copolymers therefore show a higher flow rate and lower viscosity, but without any further increase in spread, compared to the same mineral binder compositions composed in each case of the same amount of water but without any copolymer. This means that after the addition of the inventive copolymers, the composition flows faster and has a lower viscosity than a similar composition without the copolymer or a similar composition containing a non-inventive copolymer, such as a polycarboxylic ether (PCE).
[0025] In the case of the inventive use, the copolymers, in a dosage of 0.01 to 10% by weight, in particular 0.1 to 7% by weight or 0.2 to 5% by weight, respectively based on the total weight of the mineral binder, preferably influence the spread according to DIN EN 12350-5 and / or the slump according to DIN EN 12350-2 of the mineral binder composition by less than 15%, in particular less than 10%, preferably less than 5%, in particular less than 3% or less than 2%. This means that the spread and / or slump of the mineral binder composition after the addition of 0.01 to 10% by weight, in particular 0.1 to 7% by weight or 0.2 to 5% by weight of the inventive copolymer, respectively based on the total weight of the mineral binder, varies by less than 15%, in particular less than 10%, preferably less than 5%, in particular less than 3% or less than 2% from the spread and / or slump of a similar composition without the inventive copolymer.
[0026] The copolymers of the present invention can be prepared in a multi-stage operation comprising the steps of: (1) optionally, a compound of the general formula R 1 A starting material S selected from the group consisting of alcohols, amines, carboxylic acids or amides of formula -XH is reacted with an alkoxylating agent and / or a halogenated alcohol or halogenated amine Hal-R 2 -XH, wherein R 1 = C1-C18 alkyl, C2-C18 alkylene, C3-C10 cycloalkyl, C6-C30 aryl, C7-C30 aralkyl or C1-C18 carbonyl, X = O or NH, Hal = Cl, Br or I, and R 2 =C1-C16 alkyl; (2) General formula R 1 reacting a starting material S selected from the group consisting of alcohols, amines, carboxylic acids or amides of formula -XH or the reaction product of step (1) with glycidol or epichlorohydrin or a mixture of glycidol and an alkoxylating agent or a mixture of epichlorohydrin and an alkoxylating agent, wherein R 1= C1 to C18 alkyl, C2 to C18 alkylene, C3 to C10 cycloalkyl, C6 to C30 aryl, C7 to C30 aralkyl or C1 to C18 carbonyl, X = O or NH; (3) Optionally, reacting the reaction product of step (2) with an alkoxylating agent.
[0027] It is preferred to carry out the individual steps of the process successively without isolating or purifying the intermediates.
[0028] The reaction conditions for steps (1) to (3) may vary. For example, the reaction temperature, pressure, and / or type and amount of catalyst used in steps (1) to (3) may vary. However, it is generally preferred that the reaction temperature, pressure, and type and amount of catalyst used in steps (1) to (3) are the same.
[0029] The reaction temperature may vary within the range of from 80° C. to 180° C., in particular from 100° C. to 140° C. The pressure is preferably in the range of from 1 to 5 bar, in particular in the range of from 1 to 3 bar.
[0030] The individual steps of the process are preferably carried out under catalysis. Suitable catalysts for the alkoxylation of steps (1) to (3) are known per se to the person skilled in the art. In a preferred embodiment, reaction steps (1) to (3) are catalyzed. It is particularly preferred to utilize the same catalyst in steps (1) to (3) without removing or deactivating the intermediates. Particularly suitable catalysts have been found to be alkali metal hydroxides and / or alkali metal alkoxides. In a preferred embodiment, the catalyst used is the alkali metal alkoxide of the alcohol also used as starting material S. It may also be preferred to use sodium alkoxides as catalyst, in particular sodium methoxide or sodium ethoxide.
[0031] Suitable processes for preparing the copolymers of the invention are specified, for example, in EP-A-0116978.
[0032] The starting material S in this context has the general formula R 1 is a compound selected from the group consisting of alcohols, amines, carboxylic acids or amides of formula -XH, wherein R 1 =C1-C18 alkyl, C2-C18 alkylene, C3-C10 cycloalkyl, C6-C30 aryl, C7-C30 aralkyl or C1-C18 carbonyl, X=O or NH. It is particularly preferred that the starting material S does not contain any further nucleophilic groups, except for the XH group. If the starting material S is an alcohol, it is a monool, i.e. an alcohol with only one OH group. If the starting material S is an amine, it is a primary amine, i.e. an amine with an NH2 group. The starting material S is not a secondary or tertiary amine. If the starting material S is a carboxylic acid, it is a monocarboxylic acid.
[0033] In a particularly preferred embodiment, the starting material S is methanol, ethanol, n-propanol, i-propanol, n-butanol, 2-butanol, prenol, isoprenol, n-hexanol, cyclohexanol, n-octanol, 2-ethylhexanol, lauryl alcohol, myristyl alcohol, geraniol, citronellol, cetyl alcohol, stearyl alcohol, vinyl alcohol, allyl alcohol, methallyl alcohol, palmitoleyl alcohol, oleyl alcohol, linoleyl alcohol , linolenyl alcohol, phenol, benzyl alcohol, 4-methylbenzyl alcohol, anise alcohol, vanillin, methylamine, ethylamine, butylamine, cyclohexylamine, oleylamine, aniline, formic acid, acetic acid, propionic acid, butyric acid, valeric acid, isovaleric acid, caproic acid, 2-ethylhexanoic acid, caprylic acid, lauric acid, myristic acid, palmitic acid, stearic acid, oleic acid, linoleic acid, acrylic acid, methacrylic acid, benzoic acid, acrylamide, methacrylamide.
[0034] An alkoxylating agent in the context of the present invention is a compound that can be converted into a polyether by polymerization. Thus, the alkoxylating agent brings about alkoxylation, i.e. the formation of alkylene oxide or polyalkylene oxide units. In particular, the alkoxylating agent in the context of the present invention comprises an oxirane, oxetane or oxolane structure. Particularly preferred alkoxylating agents are alkylene oxides selected from ethylene oxide, propylene oxide, 1,2-butylene oxide, cyclohexene oxide and / or tetrahydrofuran. In particular, the alkoxylating agent is ethylene oxide and / or propylene oxide. It may be preferred to use only one alkoxylating agent in one of steps (1) to (3). In a very preferred embodiment, only one alkoxylating agent, in particular ethylene oxide, is used in steps (1) to (3). Alternatively, it is possible to use two or more alkoxylating agents in steps (1) to (3), either as a mixture or each individually, in any one of steps (1) to (3).
[0035] Particularly preferably, the starting material S is selected from ethoxylated methanol, ethoxylated ethanol, ethoxylated vinyl alcohol, ethoxylated allyl alcohol, ethoxylated methallyl alcohol, ethoxylated isoprenol, ethoxylated acrylic acid and ethoxylated methacrylic acid. Most preferably, the starting material S is selected from ethoxylated methanol and ethoxylated methallyl alcohol.
[0036] In a preferred embodiment, the copolymer of the present invention is prepared without the use of epichlorohydrin. Thus, the preparation process does not include epichlorohydrin. Thus, the copolymer of the present invention can be preferably prepared by a process including the following steps: (1) optionally, a compound of the general formula R 1 A starting material S selected from the group consisting of alcohols, amines, carboxylic acids or amides of formula -XH is reacted with an alkoxylating agent and / or a halogenated alcohol or halogenated amine Hal-R 2 -XH, where R1 = C1-C18 alkyl, C2-C18 alkylene, C3-C10 cycloalkyl, C6-C30 aryl, C7-C30 aralkyl or C1-C18 carbonyl, X = O or NH, Hal = Cl, Br or I, and R 2 =C1-C16 alkyl; (2) General formula R 1 reacting a starting material S selected from the group consisting of alcohols, amines, carboxylic acids or amides of -XH, or the reaction product of step (1), with glycidol or a mixture of glycidol and an alkoxylating agent, wherein R 1 =C1 to C18 alkyl, C2 to C18 alkylene, C3 to C10 cycloalkyl, C6 to C30 aryl, C7 to C30 aralkyl or C1 to C18 carbonyl, X=O or NH; (3) optionally reacting the reaction product of step (2) with an alkoxylating agent.
[0037] In a particularly preferred embodiment, the copolymers of the present invention are prepared using an alcohol as starting material S without the use of epichlorohydrin. The preparation process therefore does not involve epichlorohydrin. The copolymers of the present invention can therefore more preferably be prepared by a process comprising the following steps: (1) Optionally, alcohol R 1 -OH is alkoxylated with an alkoxylating agent and / or a halogenated alcohol or halogenated amine Hal-R 2 -XH, where R 1 = C1-C18 alkyl, C2-C18 alkylene, C3-C10 cycloalkyl, C6-C30 aryl, or C7-C30 aralkyl, X = O or NH, Hal = Cl, Br, or I, and R 2 =C1-C16 alkyl; (2) Alcohol R 1 -OH, or reacting the reaction product of step (1) with glycidol or a mixture of glycidol and an alkoxylating agent, wherein R 1=C1 to C18 alkyl, C2 to C18 alkylene, C3 to C10 cycloalkyl, C6 to C30 aryl, or C7 to C30 aralkyl; (3) optionally reacting the reaction product of step (2) with an alkoxylating agent.
[0038] In a further particularly preferred embodiment, the copolymers of the invention are prepared without the use of epichlorohydrin, using an amine as starting material S. The preparation process therefore does not involve epichlorohydrin. The copolymers of the invention can therefore also be more preferably prepared by a process comprising the following steps: (1) optionally, an amine R 1 -NH2 with an alkoxylating agent and / or a halogenated alcohol or halogenated amine Hal-R 2 -XH, where R 1 = C1-C18 alkyl, C2-C18 alkylene, C3-C10 cycloalkyl, C6-C30 aryl, or C7-C30 aralkyl, X = O or NH, Hal = Cl, Br, or I, and R 2 =C1-C16 alkyl; (2) Amine R 1 -NH2, or the reaction product of step (1) with glycidol or a mixture of glycidol and an alkoxylating agent, wherein R 1 =C1 to C18 alkyl, C2 to C18 alkylene, C3 to C10 cycloalkyl, C6 to C30 aryl, or C7 to C30 aralkyl; (3) optionally reacting the reaction product of step (2) with an alkoxylating agent.
[0039] In a further particularly preferred embodiment, the copolymers of the invention are prepared using a carboxylic acid as starting material S without the use of epichlorohydrin. The preparation process therefore does not involve epichlorohydrin. The copolymers of the invention can therefore also be prepared, more preferably, by a process comprising the following steps: (1) optionally, a carboxylic acid R 1-OH is replaced by an alkoxylating agent and / or a halogenated alcohol or halogenated amine Hal-R 2 -XH, where R 1 = C1 to C18 carbonyl, X = O or NH, Hal = Cl, Br or I, and R 2 =C1-C16 alkyl; (2) Carboxylic acid R 1 -OH, or reacting the reaction product of step (1) with glycidol or a mixture of glycidol and an alkoxylating agent, wherein R 1 =C1 to C18 carbonyl, (3) optionally reacting the reaction product of step (2) with an alkoxylating agent.
[0040] In a very particularly preferred embodiment, the copolymers of the invention are prepared using alcohols as starting materials S without the use of epichlorohydrin, in which case the starting material alcohol is first reacted with an alkoxylating agent. The preparation process therefore does not involve epichlorohydrin. Thus, the copolymers of the invention can even more preferably be prepared by a process comprising the following steps: (1) Alcohol R 1 reacting —OH with an alkoxylating agent, where R 1 =C1 to C18 alkyl, C2 to C18 alkylene, C3 to C10 cycloalkyl, C6 to C30 aryl, or C7 to C30 aralkyl; (2) reacting the reaction product of step (1) with glycidol or a mixture of glycidol and an alkoxylating agent; (3) optionally reacting the reaction product of step (2) with an alkoxylating agent.
[0041] It is particularly preferred herein if the process for preparing the copolymer of the present invention comprises step (3) above.
[0042] Thus, the copolymer of the invention obtainable by the above process may be a copolymer of general structure (I): [ka] During the ceremony, R 1 =C1 to C18 alkyl, C2 to C18 alkylene, C3 to C10 cycloalkyl, C6 to C30 aryl, C7 to C30 aralkyl or C1 to C18 carbonyl, preferably methyl, ethyl, vinyl, allyl, methallyl, isoprenyl, cyclohexyl, phenyl, acryloyl or methacryloyl; X=O or NH, Each A is independently a C1 to C10 alkylene, preferably ethylene, propylene and / or butylene; R 2 =C1-C16 alkyl, B's are each independently a C1 to C10 alkylene, preferably ethylene, propylene and / or butylene; R 3 =H, C1-C16 alkyl, or C(O)R 1 and R 1 is defined above and is preferably H, m is independently an integer ranging from 0 to 350; n is an integer ranging from 0 to 100; p is 0 or 1; q is an integer ranging from 1 to 10; When q=1, o is an integer in the range of 1 to 50, and when q>1, each o is independently an integer in the range of 1 to 50.
[0043] If n>0, it is particularly preferred that p=0.
[0044] Linear structural unit (BO) of general structure (I) m The number of depends on o and q. Structural unit (BO) m The number of units is equal to o×q+1. mThe number of q and o corresponds to the level of branching. Since each of q and o is greater than 0, the level of branching of the copolymer of the present invention is at least 2. In other words, the copolymer of the present invention is not a linear copolymer. More specifically, the copolymer of the present invention is not a purely linear polyether.
[0045] For better illustration, below are some exemplary structures derived from general formula (I) with defined combinations of o and q. These exemplary structures should not be considered as limiting in any way with respect to the copolymers of the present invention.
[0046] When o=2 and q=1, this gives a copolymer of general structure (Ia): [ka]
[0047] When o=3 and q=1, this gives a copolymer of general structure (Ib): [ka]
[0048] When o=1 and q=2, this gives a copolymer of general structure (Ic): [ka]
[0049] When o=2 and q=3, this gives a copolymer of general structure (Id): [ka]
[0050] According to an embodiment, the level of branching of the copolymers of the invention is 2-501, preferably 2-200, more preferably 2-100, particularly preferably 3-50, in particular 5-20.
[0051] It will be apparent to those skilled in the art that the reaction in step (2) of the process for preparing the copolymer of the present invention can give rise to various positional isomers, which are formed when the oxirane ring of glycidol is opened through various carbon atoms according to reaction scheme a) or b) as shown below. [ka]
[0052] For simplicity, in the present invention, only the positional isomer b) is depicted so far, however, what is always meant is both the positional isomers a) and b) or a mixture thereof.
[0053] Preferred copolymers of the present invention are copolymers of general structure (I), wherein: R 1 is selected from C1 to C18 alkyl, more preferably methyl or ethyl; X=O, Each A is independently ethylene, propylene and / or butylene, more preferably ethylene; each B is independently ethylene, propylene and / or butylene, more preferably ethylene; R 3 is H, m is independently an integer ranging from 0 to 350, more preferably from 2 to 200, even more preferably from 5 to 150, particularly preferably from 7 to 30; n is an integer ranging from 1 to 100, more preferably from 2 to 75, and most preferably from 5 to 55; p=0, q is an integer ranging from 1 to 10, more preferably from 2 to 8, and most preferably from 4 to 7; o is an integer ranging from 1 to 50, more preferably from 3 to 40, even more preferably from 6 to 30, and particularly preferably from 8 to 20.
[0054] Linear structural unit (BO) of general structure (I) m The number of depends on o and q. Structural unit (BO) m The number of is equal to o×p+1.
[0055] The structural elements (AO) and (BO) of the general structure (I) are polyalkylene oxide chains. Preferably, based on all alkylene oxide units present, the proportion of ethylene oxide units in the polyalkylene oxide chain is greater than 90 mol%, in particular greater than 95 mol%, preferably greater than 98 mol%, in particular 100 mol%. In a particular embodiment, the polyalkylene oxide chain does not have any hydrophobic groups, in particular any alkylene oxides having 3 or more carbon atoms. A high proportion of ethylene oxide units or a low content of alkylene oxides having 3 or more carbon atoms reduces the risk of unwanted air introduction.
[0056] In this context, the weight average molecular weight (M w ) is determined by gel permeation chromatography (GPC) using polyethylene glycol (PEG) as standard. This technique is known per se to the person skilled in the art. The copolymers of the invention have a molar mass M in the range of 200 to 40,000 g / mol. w In the preferred copolymers, the parameters n, m, o and p of the general structure (I) correspond to the average molar mass M w is selected to be in the range of 200 to 75,000, preferably 500 to 50,000, particularly preferably 1,000 to 35,000, even more preferably 1,500 to 25,000, and especially 2,000 to 15,000.
[0057] R 1 Copolymers of general structure (I) in which are methyl or ethyl units are particularly preferred.
[0058] In a preferred embodiment, the copolymers of the present invention are of general structure (I) where p=0 when n>0 and p=1 when n=0. Thus, in this embodiment, each copolymer contains (AO) m Unit or R2 -X units are present.
[0059] In a more preferred embodiment, all m are selected such that the average number of (BO) units in each of the o×q+1 linear structures is the same.
[0060] According to a preferred embodiment, the copolymer of the present invention is a copolymer of general structure (I), wherein R 1 is selected from C1 to C18 alkyl, more preferably methyl or ethyl; X=O, Each A is independently ethylene, propylene, and / or butylene, more preferably ethylene; each B is independently ethylene, propylene and / or butylene, more preferably ethylene; R 3 is H, m is independently an integer ranging from 0 to 350, more preferably from 2 to 200, even more preferably from 5 to 150, particularly preferably from 7 to 30; n is an integer ranging from 1 to 100, more preferably from 2 to 75, and most preferably from 5 to 55; p=0, o is an integer ranging from 1 to 50, more preferably from 3 to 40, even more preferably from 6 to 30, and particularly preferably from 8 to 20, and q=1. Such copolymers conform to the general structure (II): [ka]
[0061] The copolymers of general structure (II) can be prepared by a process comprising the steps of: (1) Alcohol R 1 reacting —OH with an alkoxylating agent, preferably ethylene oxide, where R 1 =C1-C18 alkyl, preferably methyl or ethyl; (2) Reacting the reaction product of step (1) with glycidol, (3) Reacting the reaction product of step (2) with an alkoxylating agent, preferably ethylene oxide.
[0062] According to a more preferred embodiment, the copolymer of the present invention is a copolymer of general structure (I), wherein, R 1 is selected from C1-C18 alkyl, more preferably methyl or ethyl, X = O, A is each independently ethylene, propylene, and / or butylene, more preferably ethylene, B is each independently ethylene, propylene and / or butylene, more preferably ethylene, R 3 is H, m is each independently an integer in the range of 0-350, more preferably 2-200, even more preferably 5-150, particularly 7-30, n is an integer in the range of 1-100, more preferably 2-75, most preferably 5-55, p = 0, o is an integer in the range of 1-50, more preferably 3-40, even more preferably 6-30, particularly 8-20, and q is at least 2. Such a copolymer has the general structure (III)
Chemical formula
[0063] The copolymer of general structure (III) can be prepared by a process comprising the following steps: (1) Reacting the alcohol R 1 -OH with an alkoxylating agent, preferably ethylene oxide, where R 1 = C1-C18 alkyl, preferably methyl or ethyl, (2) reacting the reaction product of step (1) with a mixture of glycidol and an alkoxylating agent, preferably ethylene oxide; (3) reacting the reaction product of step (2) with an alkoxylating agent, preferably ethylene oxide.
[0064] According to a further preferred embodiment, the copolymer of the present invention is a copolymer of general structure (I), wherein R 1 is selected from C2-C18 alkenyl, more preferably vinyl, allyl, methallyl, or isoprenyl, in particular methallyl; X=O, each B is independently ethylene, propylene and / or butylene, more preferably ethylene; R 2 is C1-C16 alkyl, more preferably C2-C4 alkyl, in particular butyl; R 3 is H, m is independently an integer ranging from 0 to 350, more preferably from 2 to 200, even more preferably from 5 to 150, particularly preferably from 7 to 30; n=0, p=1, o is an integer ranging from 1 to 50, more preferably from 3 to 40, even more preferably from 6 to 30, and particularly preferably from 8 to 20; Such copolymers conform to the general structure (IV): [ka]
[0065] Copolymers of general structure (IV) can be prepared by a process comprising the steps of: (1) Alcohol R 1 -OH to halogenated alcohol Hal-R 2 -XH, where R 1 = C2-C18 alkenyl, R 2is C1-C16 alkyl, Hal is Cl, Br or I, and X is O; (2) reacting the reaction product of step (1) with glycidol; (3) reacting the reaction product of step (2) with an alkoxylating agent, preferably ethylene oxide.
[0066] According to a further preferred embodiment, the copolymer of the present invention is a copolymer of general structure (I), wherein R 1 is selected from C1 to C18 alkyl, more preferably methyl or ethyl; X=O, each B is independently ethylene, propylene and / or butylene, more preferably ethylene; R 2 is C1-C16 alkyl, more preferably C2-C4 alkyl, in particular butyl; R 3 is H, m is independently an integer ranging from 0 to 350, more preferably from 2 to 200, even more preferably from 5 to 150, particularly preferably from 7 to 30; n=0, p=0, q is an integer ranging from 1 to 10; Each o is independently an integer of 1 to 50, more preferably 3 to 40, even more preferably 6 to 30, and particularly preferably 8 to 20. Such copolymers conform to the general structure (V): [ka]
[0067] Copolymers of general structure (V) can be prepared by a process comprising the steps of: (1) Alcohol R 1 reacting -OH with glycidol; (2) reacting the reaction product of step (1) with an alkoxylating agent, preferably ethylene oxide.
[0068] According to a very particularly preferred embodiment, the copolymer of the invention is a copolymer of general structure (I), in which R 1 is selected from methyl, X=O, A is ethylene; B is ethylene; R 3 is H, m is independently an integer ranging from 5 to 20; n=5, p=0, o=an integer in the range of 3 to 10; q=1.
[0069] Such copolymers conform to the general structure (VI): [ka]
[0070] Copolymers of general structure (VI) can be prepared by a process comprising the steps of: (1) reacting methanol with ethylene oxide; (2) reacting the reaction product of step (1) with glycidol; (3) reacting the reaction product of step (2) with ethylene oxide.
[0071] The mineral binder composition is in particular a workable and / or aqueous mineral binder composition.
[0072] The mineral binder composition comprises at least one mineral binder. The expression "mineral binder" is understood in particular to mean a binder that reacts in the presence of water in a hydration reaction to give a solid hydrate or hydrate phase. It can be, for example, a hydraulic binder (for example cement or hydraulic lime), a potentially hydraulic binder (for example slag), a pozzolanic binder (for example fly ash) or a non-hydraulic binder (gypsum or white lime).
[0073] More specifically, the mineral binder or binder composition comprises a hydraulic binder, preferably a cement. Particularly preferred is a cement with a cement clinker content of 35% by weight or more. More specifically, the cement is of type CEM I, CEM II and / or CEM III, CEM IV or CEM V (according to standard EN197-1).
[0074] The mineral binder composition comprises at least one hydraulic binder, preferably cement, in an amount of at least 5 wt.-%, preferably at least 20 wt.-%, more preferably at least 35 wt.-%, even more preferably at least 65 wt.-%, in particular 95 wt.-% or more, each based on the dry weight of the mineral binder composition.
[0075] Alternatively, it may be advantageous if the mineral binder or the mineral binder composition comprises or essentially consists of other binders. These are in particular potentially hydraulic and / or pozzolanic binders. Suitable potentially hydraulic and / or pozzolanic binders are, for example, slag, fly ash and / or silica dust. The binder composition may likewise comprise inert substances, for example limestone, quartz flour and / or pigments. In an advantageous embodiment, the mineral binder comprises 5 to 95% by weight, in particular 5 to 65% by weight, more preferably 15 to 35% by weight, respectively, of potentially hydraulic and / or pozzolanic binders, based on the total weight of the binder. Advantageous potentially hydraulic and / or pozzolanic binders are slag and / or fly ash.
[0076] In a particularly preferred embodiment, the mineral binder comprises a hydraulic binder, in particular cement or cement clinker, and a potentially hydraulic and / or pozzolanic binder, preferably slag and / or fly ash, in which case the proportion of potentially hydraulic and / or pozzolanic binder is more preferably 5-65% by weight, more preferably 15-35% by weight, while at least 35% by weight, in particular at least 65% by weight, of hydraulic binder is present.
[0077] The mineral binder composition is preferably a mortar or concrete composition, in particular a mortar or concrete composition with a low weight ratio of water to binder (w / b ratio). Specific examples include high performance concrete (HPC), ultra high performance concrete (UHPC) or self-compacting concrete (SCC). The mineral binder composition is in particular a processable mineral binder composition and / or a mineral binder composition that is composed of water.
[0078] Thus, in a very particularly preferred embodiment, the mineral binder composition comprises water. The weight ratio of water to binder (w / b ratio) in the mineral binder composition is preferably in the range of 0.18 to 0.6, more preferably 0.2 to 0.5, even more preferably 0.22 to 0.4, in particular 0.22 to 0.37, in particular 0.22 to 0.28 or 0.32 to 0.37.
[0079] The copolymer according to the invention is advantageously present in an amount of 0.01 to 10% by weight, in particular 0.1 to 7% by weight or 0.2 to 5% by weight, each based on the total weight of the mineral binder.
[0080] In a preferred embodiment, the mineral binder composition preferably has a density of 250 kg / m 3 Ultra, especially 350-600kg / m 3 The cement content here is in particular 200-800 kg / m 3 , preferably 320 to 500 kg / m 3 It is.
[0081] Fines include fly ash, metakaolin, silica dust, and / or inert rock flour, among others.
[0082] More specifically, the fine powder has the fineness of cement, more specifically, the maximum particle diameter of the fine powder, as measured, for example, by laser granulometry, is less than 0.125 mm.
[0083] The fine powder preferably has a density of at least 1,000 cm 2 / g, especially at least 1,500 cm 2 / g, preferably at least 2,500 cm 2 / g, more preferably at least 3,500 cm 2 / g or at least 5,000 cm 2 It has a Blaine fineness of 1.0 / g.
[0084] The copolymers of the present invention have zero or low water reducing ability, which is advantageous since they can be used to reduce the viscosity of per se known mineral binder compositions that contain water reducers, for example superplasticizers, without the need to adjust the amount of superplasticizer or water.
[0085] In a further preferred embodiment, the mineral binder composition therefore further comprises at least one high-performance plasticizer selected from the group of lignosulfonates, polynaphthalenesulfonates, polymelaminesulfonates and / or polycarboxylic acid ethers, in particular at least one polycarboxylic acid ether.
[0086] Polycarboxylate ethers are comb polymers having a polycarboxylate backbone and polyalkylene oxide side chains.
[0087] Preferred polycarboxylic acid ethers include structural units of formula VII and structural units of formula VIII, [ka] During the ceremony, R4 are each independently -COOM, -SO2-OM, -O-PO(OM)2 and / or -PO(OM)2, preferably -COOM; R 5 are each independently H, -CH-COOM, or an alkyl group having 1 to 5 carbon atoms, preferably H or CH; R 6 are each independently H or an alkyl group having 1 to 5 carbon atoms, preferably H; R 7 are each independently H, -COOM, or an alkyl group having 1 to 5 carbon atoms, preferably H; Or R 4 and R 7 forms a ring to give -CO-O-CO- (anhydride), M is independently H + , alkali metal ions, alkaline earth metal ions, divalent or trivalent metal ions, ammonium groups or organic ammonium, preferably H + or an alkali metal ion, r=0, 1 or 2; s=0 or 1, t=0 or an integer from 1 to 4; u=2~250, especially 10~200; Each Y is independently -O- or -NH-; R 8 are each independently H, C1 to C 20 an alkyl group, a cyclohexyl group, or an alkylaryl group; D=C2-C4 alkylene, preferably ethylene.
[0088] The molar ratio of the structural unit VII to the structural unit VIII is preferably 0.7 to 10:1, more preferably 1 to 8:1, and particularly preferably 1.5 to 5:1.
[0089] It may also be advantageous if the polycarboxylic acid ether further comprises a structural unit IX, which is preferably derived from a monomer selected from the group consisting of alkyl or hydroxyalkyl esters of acrylic or methacrylic acid, vinyl acetate, styrene and N-vinylpyrrolidone.
[0090] The polycarboxylic acid ethers preferably contain carboxylic acid groups and / or salts thereof and polyethylene glycol side chains.
[0091] Preferably, the polycarboxylic acid ether is composed of a structural unit VII derived from an ethylenically unsaturated carboxylic acid, particularly an unsaturated monocarboxylic acid or a salt thereof, and a structural unit VIII derived from an ethylenically unsaturated polyalkylene glycol, particularly a polyethylene glycol. In particular, the polycarboxylic acid ether does not contain any other structural units except for the structural units VII and VIII.
[0092] High-performance fluidizers, in particular polycarboxylic ethers, can be added to the mineral binder composition in an amount of 0 to 10% by weight, preferably 0.1 to 8% by weight, in particular 0.25 to 7% by weight, calculated as the dry weight of fluidizer, based on the total weight of the mineral binder composition.
[0093] Thus, in a further aspect, the present invention relates to the use of the inventive copolymer in a mineral binder composition comprising a high-performance plasticizer, in particular at least one polycarboxylic acid ether, selected from the group of lignosulfonates, polynaphthalenesulfonates, polymelaminesulfonates and / or polycarboxylic acid ethers.
[0094] It is possible to add the copolymer of the present invention as such to the mineral binder composition, or to add the copolymer of the present invention to the mineral binder composition as an aqueous solution or emulsion in water, or to dissolve or disperse the copolymer of the present invention in an additive, particularly an aqueous additive.
[0095] Thus, a further aspect of the present invention is an additive comprising at least one copolymer prepared in a multi-stage operation comprising the steps of: (1) optionally, a compound of the general formula R 1 A starting material S selected from the group consisting of alcohols, amines, carboxylic acids or amides of formula -XH is reacted with an alkoxylating agent and / or a halogenated alcohol or halogenated amine Hal-R 2 -XH, where R 1 = C1-C18 alkyl, C2-C18 alkylene, C3-C10 cycloalkyl, C6-C30 aryl, C7-C30 aralkyl or C1-C18 carbonyl, X = O or NH, Hal = Cl, Br or I, and R 2 =C1-C16 alkyl; (2) General formula R 1 reacting a starting material S selected from the group consisting of alcohols, amines, carboxylic acids or amides of -XH or the reaction product of step (1) with glycidol or epichlorohydrin or a mixture of glycidol and an alkoxylating agent or a mixture of epichlorohydrin and an alkoxylating agent, where R 1 =C1 to C18 alkyl, C2 to C18 alkylene, C3 to C10 cycloalkyl, C6 to C30 aryl, C7 to C30 aralkyl or C1 to C18 carbonyl, X=O or NH; (3) optionally reacting the reaction product of step (2) with an alkoxylating agent.
[0096] Furthermore, the additive may comprise at least one polycarboxylic ether and / or water. The additive may be used as a dispersant for the mineral binder, in which case it may simultaneously reduce the viscosity and the demand for water.
[0097] Preferably, the weight ratio of the copolymer of the invention to the polycarboxylic ether in the aqueous additive ranges from 0.05:5 to 1:1, preferably from 0.1:3 to 1:1, more preferably from 0.1:3 to 1:3.
[0098] In a further aspect, the present invention relates to a composition, in particular a mortar composition, a concrete composition or a cement-based composition, comprising at least one copolymer as defined above and a mineral binder, the mineral binder being preferably a hydraulic binder, in particular a cement, preferably Portland cement.
[0099] The composition is in particular a high performance concrete, an ultra high performance concrete or a self-compacting concrete.
[0100] The copolymer advantageously has a proportion of 0.01 to 10% by weight, in particular 0.1 to 7% by weight or 0.2 to 5% by weight, based on the weight of the mineral binder.
[0101] In particular, the composition preferably has a viscosity of 350 kg / m 3 Ultra-high, especially 400-600kg / m 3 The cement content here is, in particular, 320-380 kg / m 3 It is.
[0102] A further aspect relates to a method for controlling the rheology of a mineral binder composition, in particular HPC, UHPC or SCC, characterized in that at least one copolymer of the invention is added to a dry mix of the mineral binder composition and / or is added to the mineral binder composition together with the mixing water, in particular as an aqueous solution or an emulsion in the mixing water, and / or is added to the mineral binder composition immediately after the addition of the mixing water. Controlling the rheology is understood in this context to mean that the addition of the copolymer of the invention reduces the viscosity of the respective mineral binder composition, in particular measured as funnel flow time according to DIN EN 12350-9 and / or running time according to JSCE F 541-1999, or increases the flowability without significantly changing the spread measured according to DIN EN 12350-5 and / or the slump measured according to DIN EN 12350-2. In other words, the expression "controlling the rheology" in this context means an increase in the flow rate and a decrease in the viscosity of the mineral binder composition. Preferably, "controlling the rheology" in this context is understood to mean increasing the flow rate and decreasing the viscosity without a significant change in the spread and / or slump of the mineral binder composition. "Dry mix" is understood to mean a mineral binder composition comprising all the components of the mineral binder composition except water.
[0103] More specifically, in the inventive method for controlling the rheology of a mineral binder composition, in particular HPC, UHPC or SCC, at a dosage of the inventive copolymer of 0.01 to 10 wt.-%, in particular 0.1 to 7 wt.-% or 0.2 to 5 wt.-%, respectively based on the total weight of the mineral binder, the funnel flow time according to DIN EN 12350-9 is reduced by at least 5%, preferably at least 10%, more preferably at least 15% and / or the run time according to JSCE-F 541-1999 of the mineral binder composition is reduced by at least 10%, preferably at least 15%, more preferably at least 25%, in particular at least 30%, compared to the funnel flow time and / or the running time of a similar composition not comprising the inventive copolymer.
[0104] Furthermore, in the inventive method for controlling the rheology of a mineral binder composition, in particular HPC, UHPC or SCC, at a dosage of the inventive copolymer of 0.01 to 10 wt.-%, in particular 0.1 to 7 wt.-% or 0.2 to 5 wt.-%, respectively based on the total weight of the mineral binder, the spread according to DIN EN 12350-5 and / or the slump according to DIN EN 12350-2 of the mineral binder composition compared to the spread and / or slump of a similar composition not comprising the inventive copolymer varies by less than 15%, in particular less than 10%, preferably less than 5%, in particular less than 3% or less than 2%.
[0105] A further aspect relates to a moulded body which can be obtained by curing, after addition of water, a mineral binder composition as described above, in particular HPC, UHPC or SCC, which comprises at least one copolymer according to the invention.
[0106] Hereinafter, the present invention will be described in detail by means of examples. However, the examples are merely useful for illustration and should not be construed as limiting the scope of the present invention. EXAMPLES
[0107] Example 1 - Preparation of the copolymers used Preparation of C-1 Step 1: In a reactor inerted with N2 gas, 4 g (0.074 mol) of sodium methoxide are dissolved in 576 g (8 mol) of methallyl alcohol and heated to 100 ° C. This is followed by the metered addition of 1760 g (40 mol) of ethylene oxide over a period of 5 hours, during which the temperature is maintained at 100-140 ° C and the pressure at 1-3 bar. After the metered addition is over, the reaction mixture is stirred at 140 ° C for 2 hours. The mixture is then cooled to 30 ° C.
[0108] Step 2: In a reactor inerted with N2 gas, 0.54 g (0.01 mol) of sodium methoxide is added to 123 g (0.42 mol) of the mixture from step (1) and heated to 130 °C. This is followed by metered addition of 93 g (1.26 mol) of glycidol over a period of 30 minutes. During this time, the temperature is maintained at 130-140 °C and the pressure at 1-3 bar. After the metered addition is complete, the reaction mixture is stirred at 140 °C for 2 hours. The mixture is left to cool to 50 °C.
[0109] Step 3: After cooling to 50°C, 2.2 g (0.04 mol) of sodium methoxide is added to the mixture of step (2). The reactor is again inerted with N2 gas and heated to 130°C. This is followed by metered addition of 628 g (14.27 mol) of ethylene oxide over a period of 4 hours. During this time, the temperature is maintained at 130-140°C and the pressure at 0-3 bar. After the metered addition is over, the reaction mixture is stirred at 140°C for 3 hours. The mixture is then cooled to 50°C and neutralized with 3.2 g (0.054 mol) of acetic acid. The resulting mixture is copolymer C-1 of the invention.
[0110] Preparation of C-2 The preparation of C-2 is similar to that of C-1, except that in step (3), 2513 g of ethylene oxide (57 moles) is weighed to prepare C-2.
[0111] Preparation of C-4 The preparation of C-4 is similar to that of C-1, except that 256 g of methanol (8 moles) is used in place of methallyl alcohol in step (1).
[0112] Preparation of C-5 The preparation of C-5 is similar to that of C-4, except that in step (3), 2513 g of ethylene oxide (57 moles) is weighed to prepare C-5.
[0113] Preparation of C-6 The preparation of C-6 is similar to that of C-5, except that in step (2), 186 g (2.51 moles) of glycidol is weighed out to prepare C-6.
[0114] Table 1 below provides an overview of the PCEs and copolymers used as additives.
[0115] [Table 1-1]
[0116] [Table 1-2]
[0117] Example 2 - Paste Test A dry mix was made consisting of 150 g cement (CEM I 42.5N from Vigier Holding AG), 5.8 g microsilica (SikaFume®-HR / -TU, available from Sika Schweiz AG), 69.2 g blast furnace slag (Regen GGBS from Hanson UK), and 41.5 g limestone (Nekafill 15 from Kalkfabrik Netstal AG). To make the dry mix, the ingredients were dry mixed in a Hobart mixer for 30 seconds. To this dry mix, the additives specified in Table 2 were added, each dissolved in 60 g water. Mixing continued for 30 seconds at level 1 and finally for 3.5 minutes at level 2.
[0118] The flow time according to DIN EN 12350-9 and the spread according to DIN EN 12350-5 were determined on the resulting cement pastes. In each case, the time was measured after 210 g of the respective mixtures V1 to V3 (not according to the invention) or E1 to E3 (according to the invention) had completely disappeared. The results are summarized in Table 2 below.
[0119] [Table 2]
[0120] It becomes evident from table 2 that the use of the copolymers according to the invention in the experiments E1 to E3 leads to an increase in flowability or a decrease in flow time corresponding to a decrease in viscosity. A comparison is now made with the non-inventive reference V1, which contains only PCE and no copolymer according to the invention. Moreover, it becomes evident from table 2 that the copolymers according to the invention do not cause any further liquefaction, i.e. no decrease in the water demand. Finally, it becomes evident from table 2 that the use of polyethylene glycol or polypropylene glycol leads in particular to a clear increase in flow time, which corresponds to an increase in viscosity.
[0121] Example 3 - Mortar Test A dry mix was made consisting of 735 g cement (CEM I 42.5N from Vigier Holding AG), 28 g microsilica (SikaFume®-HR / -TU, available from Sika Schweiz AG), 340 g blast furnace slag (Regen GGBS from Hanson UK), 203 g limestone (Nekafill 15 from Kalkfabrik Netstal AG) and 2845 g aggregates with particle size of 0-8 mm. To make the dry mix, the ingredients were dry mixed in a Hobart mixer for 30 seconds. To this dry mix, the additives specified in Table 3 were added, each dissolved in the amount of water specified in Table 3. Mixing continued for 30 seconds at level 1 and finally for 3.5 minutes at level 2.
[0122] The spread according to DIN EN 12350-5 was determined on the mortars obtained immediately after mixing (0 min) and after 30 min. Furthermore, the funnel flow time was determined according to DIN EN 12350-9. The results are summarized in Table 3 below.
[0123] [Table 3]
[0124] Inventive experiments E4 and E5 show a clear decrease in flow time from the V-funnel compared to non-inventive experiment V4, which corresponds to improved flow or reduced viscosity. Inventive experiments E6-E11 show that improved flow or reduced viscosity can also be achieved by reducing the amount of water.
[0125] The results in Table 3 also show that the use of the copolymers of the present invention only slightly affects the spread and therefore the yield point of the mineral binder composition, with only a small shift.
[0126] Example 4 - Concrete Testing A dry mix was made consisting of 340 g cement (CEM I 42.5N from Vigier Holding AG), 851 g quartz sand, and 951 g gravel. To make the dry mix, the ingredients were dry mixed in a Hobart mixer for 30 seconds. To this dry mix, the additives specified in Table 4 were added, each dissolved in 170 g water. Mixing continued for 30 seconds at level 1 and finally for 3.5 minutes at level 2.
[0127] The concrete obtained was measured for slump according to JIS A1150 and flow rate according to JSCE-F-514. The results are summarized in Table 4 below.
[0128] [Table 4]
[0129] A comparison of the inventive experiments E13 and E14 with the non-inventive experiment V5 reveals that the inventive use of the copolymer allows a clear increase in flow rate, which corresponds to a decrease in viscosity.
[0130] Example 5 - Mortar Test The dry mix of Example 4 was passed through a sieve with a mesh size of 5 mm. To the resulting dry mix, the additives specified in Table 5 were added, each dissolved in 170 g of water. Mixed in a Hobart mixer at level 1 for 30 seconds and finally further mixed at level 2 for 3.5 minutes.
[0131] The resulting mortar mixtures were subjected to the determination of spread according to JIS A1150 and run time according to JSCE-F 541-1999. The results are summarized in Table 5 below.
[0132] [Table 5]
[0133] A comparison of the inventive experiments E15 and E16 with the non-inventive experiment V6 reveals that the inventive use of the copolymer allows a clear reduction in the outflow time, which corresponds to a reduction in viscosity.
Claims
1. Use of a copolymer as an additive for increasing the flow rate and / or reducing the viscosity of a mineral binder composition, said copolymer being prepared in a multi-stage operation comprising the steps of: (1) optionally, a group of general formula R 1 A starting material S selected from the group consisting of alcohols, amines, carboxylic acids or amides of -XH is reacted with an alkoxylating agent and / or a halogenated alcohol or halogenated amine Hal-R 2 -XH, where R 1 = C1 to C18 alkyl, C2 to C18 alkylene, C3 to C10 cycloalkyl, C6 to C30 aryl, C7 to C30 aralkyl, or C1 to C18 carbonyl, X = O or NH, Hal = Cl, Br, or I, and R 2 = C1 to C16 alkyl; (2) General formula R 1 reacting a starting material S selected from the group consisting of alcohols, amines, carboxylic acids, or amides of -XH, or the reaction product of step (1), with glycidol or a mixture of glycidol and an alkoxylating agent, where R 1 = C1 to C18 alkyl, C2 to C18 alkylene, C3 to C10 cycloalkyl, C6 to C30 aryl, C7 to C30 aralkyl, or C1 to C18 carbonyl, X = O or NH; (3) optionally reacting the reaction product of step (2) with an alkoxylating agent.
2. 2. Use of the copolymer according to claim 1, characterized in that the copolymer is a copolymer of general structure (I): 【Chemistry 1】 (In the formula, R 1 =C1-C18 alkyl, C2-C18 alkylene, C3-C10 cycloalkyl, C6-C30 aryl, C7-C30 aralkyl, or C1-C18 carbonyl; X=O or NH, Each A is independently a C1-C10 alkylene; R 2 = C1 to C16 alkyl, Each B is independently a C1-C10 alkylene; R 3 =H, C1-C16 alkyl, or C(O)R 1 and R 1 is defined above, Each m is independently an integer ranging from 0 to 350; n is an integer ranging from 0 to 100; p is 0 or 1; q is an integer ranging from 1 to 10; and When q=1, o is an integer ranging from 1 to 10, and when q>1, each o is independently an integer ranging from 1 to 50).
3. 2. Use of the copolymer according to claim 1, characterized in that the copolymer is a copolymer of general structure (II), (III) or (V): 【Chemistry 2】 (In the formula, R 1 is selected from C1-C18 alkyl; Each A is independently ethylene, propylene, and / or butylene, ethylene; B is independently ethylene, propylene, and / or butylene, ethylene; Each m is independently an integer ranging from 0 to 350; n is an integer ranging from 1 to 100; Each o is independently an integer ranging from 1 to 50; q is an integer ranging from 1 to 10; and x is an integer ranging from 1 to 9, with the proviso that x<o).
4. Use of the copolymer according to any one of claims 1 to 3, characterized in that the average molar mass Mw of said copolymer is in the range from 200 to 75,000.
5. R 1 Use of a copolymer according to any one of claims 1 to 4, characterized in that is a C1 to C18 alkyl unit.
6. Use according to any one of claims 1 to 5, characterised in that the mineral binder composition comprises at least one hydraulic binder in at least 5% by weight, each based on the dry mass of the mineral binder composition.
7. Use according to any one of the preceding claims, characterised in that the copolymer is present in an amount of 0.01 to 10% by weight, each based on the total weight of the mineral binder.
8. Use according to any one of the preceding claims, characterised in that the mineral binder composition comprises water in an amount such that the water to mineral binder ratio ranges from 0.18 to 0.
6.
9. Use according to any one of claims 1 to 8, characterised in that the mineral binder composition is a high performance concrete, an ultra high performance concrete or a self-compacting concrete.
10. 10. Use according to any one of the preceding claims, characterised in that the mineral binder composition comprises at least one superplasticiser selected from the group of lignosulfonates, polynaphthalenesulfonates, polymelaminesulfonates and / or polycarboxylic acid ethers.
11. The method of claim 1, further comprising the steps of: preparing at least one copolymer in a multi-step operation comprising the steps of: (1) optionally, a group of general formula R 1 A starting material S selected from the group consisting of alcohols, amines, carboxylic acids or amides of -XH is reacted with an alkoxylating agent and / or a halogenated alcohol or halogenated amine Hal-R 2 -XH, where R 1 = C1 to C18 alkyl, C2 to C18 alkylene, C3 to C10 cycloalkyl, C6 to C30 aryl, C7 to C30 aralkyl, or C1 to C18 carbonyl, X = O or NH, Hal = Cl, Br, or I, and R 2 = C1 to C16 alkyl; (2) General formula R 1 reacting a starting material S selected from the group consisting of alcohols, amines, carboxylic acids, or amides of -XH, or the reaction product of step (1), with glycidol or a mixture of glycidol and an alkoxylating agent, where R 1 = C1 to C18 alkyl, C2 to C18 alkylene, C3 to C10 cycloalkyl, C6 to C30 aryl, C7 to C30 aralkyl, or C1 to C18 carbonyl, X = O or NH; (3) optionally reacting the reaction product of step (2) with an alkoxylating agent; 23. A method for producing an additive for a mineral binder composition comprising:
12. 12. A method for producing an additive according to claim 11, comprising the step of adding to said copolymer at least one polycarboxylic ether, the ratio of copolymer to polycarboxylic ether being in the range of 0.05:5 to 1:
1.
13. 13. A method for controlling the rheology of a mineral binder composition, characterized in that the additive according to claim 11 and / or claim 12 is added to a dry mix of the mineral binder composition and / or together with the mixing water and / or immediately after the addition of the mixing water.
14. The method of claim 1, further comprising the steps of: preparing at least one copolymer in a multi-step operation comprising the steps of: (1) optionally, a group of general formula R 1 A starting material S selected from the group consisting of alcohols, amines, carboxylic acids or amides of -XH is reacted with an alkoxylating agent and / or a halogenated alcohol or halogenated amine Hal-R 2 -XH, where R 1 = C1 to C18 alkyl, C2 to C18 alkylene, C3 to C10 cycloalkyl, C6 to C30 aryl, C7 to C30 aralkyl, or C1 to C18 carbonyl, X = O or NH, Hal = Cl, Br, or I, and R 2 = C1 to C16 alkyl; (2) General formula R 1 reacting a starting material S selected from the group consisting of alcohols, amines, carboxylic acids, or amides of -XH, or the reaction product of step (1), with glycidol or a mixture of glycidol and an alkoxylating agent, where R 1 = C1 to C18 alkyl, C2 to C18 alkylene, C3 to C10 cycloalkyl, C6 to C30 aryl, C7 to C30 aralkyl, or C1 to C18 carbonyl, X = O or NH; (3) optionally reacting the reaction product of step (2) with an alkoxylating agent; and A method for producing a mineral binder composition comprising adding said copolymer to at least one mineral binder.
15. 15. A method for producing a compact comprising the step of hardening the mineral binder composition according to claim 14 after adding water to produce a compact.
Citation Information
Patent Citations
Crosslinked branch copolymer and manufacture
JP1984159830A
Process for producing highly branched polyols based on glycidol
JP2002533495A
Cement additive and cement composition using the same
JP2007153641A
Copolymers, their use as thickeners, and methods for producing them.
JP2012532975A
Use of ultrabranched polyether surfactants in cementitious systems
JP2014510689A